Family conflicts and the violence of unemployed husbands against their wives acting as the main breadwinner - Widi Tri Pramesti Ningrum; Siti Mas'udah (Department of Sociology, Faculty of Social and Political Sciences, Universitas Airlangga, 2021)
In a patriarchal society, men are the breadwinners and women are obliged to perform a domestic role. However, in reality, there are many families with unemployed husbands and working wives who support the family. This study aimed to reveal the background of unemployed husbands and the conflicts and violence against wives as the main breadwinner. This study used qualitative research methods and is descriptive research in design. The researchers interviewed informants from families with unemployed husbands where the wives were the breadwinners. The results of this study indicate that the causes of the husbands not working include illness, bankruptcy, company rationalization, a lack of desire to support their family or being too lazy to work. The conflicts that often occur in families with unemployed husbands include the socialization of the children, family economy, the division of domestic labor, differences of opinion in various matters, conflicts with their extended families, and various cases that are considered trivial. The violence that occurs in the family with unemployed husbands is physical violence, verbal, and psychological abuse to wives. Although the wives are the source of the family economy, the husbands remain in a dominant position in the family. Therefore, efforts to overcome the violence in the family requires support from many parties, including the wives, families, communities, and the state.